The Linkage Between Blue Economy and Digital Tourism: Platform-Based Monetization Strategies for Marine Ecosystems - Marvina Anan Dita (Nomico, 2025)
The integration of the blue economy and digital tourism has become a key driver of sustainable development in coastal regions. This study examines the interlinkage between these two concepts and explores platform-based monetization strategies for marine ecosystems. To quantitatively analyze the relationship between digital technology adoption, platform monetization efficiency, and the sustainability of marine ecosystems within the framework of the blue economy and digital tourism. This research employed a quantitative approach using Structural Equation Modeling (SEM) on 85 marine tourism destinations in Indonesia selected through purposive sampling. Data were collected through online surveys of tourism destination managers and secondary digital platform data spanning 2022–2024. The structural model demonstrated that digital technology adoption significantly influences monetization efficiency (β = 0.742, p < 0.001), which in turn positively impacts ecosystem sustainability (β = 0.631, p < 0.001). Digital platforms increased average revenue by 45–78% and operational efficiency by 32–56% across marine tourism destinations. Platform-based monetization strategies have proven effective in integrating the blue economy with digital tourism, though adequate infrastructure and skilled human resources remain prerequisites.